Control Strategy of Dual Power Supply Excitation System for HTS Synchronous Condenser - Jinfeng Wang; Hao Yin; Tiantian Cao; Zhu Liu; Dayi Li (IEEE Access)
High temperature superconducting (HTS) synchronous condenser is a novel large-capacity reactive power compensation device. Its reactive power compensation capacity and accuracy are mainly determined by the excitation system, making the excitation power supply a crucial part of the HTS synchronous condenser system. This paper presents a dual power supply excitation system for HTS synchronous condenser. The principle and control strategy of its topology are introduced, and simulation analysis is carried out. The interleaved parallel control strategy of the excitation system based on the state-space averaging method is investigated, and superconducting experiments on low-voltage power supply are conducted. Experimental results show that this control strategy can significantly reduce the exciting current ripple. For example, the current ripple is reduced to about 0.008%. When the HTS synchronous condenser operates in constant excitation mode and forced excitation mode respectively, the required voltage and current for the excitation winding differ in magnitude and accuracy. The proposed excitation system not only solves this problem but also improves the power supply utilization rate. It provides stable and high-precision excitation current, enabling the HTS synchronous condenser to accurately compensate reactive power and enhance the stability of the power grid.